Arthur's angry! - Hicks, Lesley; Moss, Jason J. (Mandaluyong City : Hiyas, 2003)
"Arthur is an angry kid. When he explodes, it's funny but scary. Arthur scares his friends away and even scares himself."--Cover.
Keywords: Children's stories